PENINGKATAN KEMAMPUAN KOGNITIF SISWA MELALUI PEMBELAJARAN ARIAS - Ravensky Yurianty Pratiwi (Orbital: Jurnal Pendidikan Kimia, 2020)
The quality of education depends on competence of teachers in managing learning. Improving the quality of learning in class can improve the quality of education. Research conducted using classroom action research with qualitative descriptive approach thats aims to find out and describe the application of the ARIAS learning model in improving students' cognitive abilities. Subjects in the study were teachers and all students of class XI IPA 2 SMA Negeri 6 Palembang. The instruments used in the research were questionnaires, observation sheets, cognitive ability tests and documentation studies. Based on the treatment given by the teacher for three cycles, it was found that the average cognitive chemical ability of students in the first cycle was 69,66. In the second and third cycles, the average chemical cognitive abilities of students were 78,84 and 84.35. Meanwhile, the percentage of learning mastery obtained in the first, second and third cycles were 52,63%, 73,68%, and 86,84%. Based on the research and data analysis conducted, it is known that the ARIAS learning model can improve students' cognitive abilities. Besides that, it can develop students' self-confidence and enthusiasm in learning chemistry.